Analisis Pengaruh Model Pembelajaran Inkuiri dan Mind Mapping terhadap Kemampuan Berpikir Kreatif pada Siswa di Sekolah Dasar - Kristiyan, Candra; Sumarno, Sumarno; Sulianto, Joko (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2025)
This study analyzes the effect of inquiry learning model and mind mapping on the creative thinking ability of fourth grade elementary school students. The research method used is a combination method (Mixed Method Research) with a classroom action research approach and experiments using the Pre-experimental One Group Pretest-Posttest Design. The results of the study indicate that there are significant differences in students' creative thinking abilities based on the learning model applied. The inquiry learning model is proven to be more effective than mind mapping and conventional methods because it encourages concept exploration, problem solving, and improves high-level thinking skills. The mind mapping model also shows advantages over conventional methods in helping students organize and visualize information. Overall, the inquiry learning model has the most positive impact on students' creativity in understanding subject matter.